The State’s Business Upon Indigenous Land in Indonesia: A Legacy from Dutch Colonial Regime to Modern Indonesian State - Fahmi, Chairul; Stoll, Peter-Tobias; Shabarullah, Shabarullah; Rahman, Malahayati; Syukri, Syukri (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2024)
The indigenous populations of Indonesia have experienced the deprivation of their rights to their ancestral lands since the era of Dutch colonialism. This article seeks to analyse the occurrence of the rights of indigenous peoples to their ancestral territories, and the state’s right claim over indigenous customary lands. This study is a qualitative method with a socio-legal research approach, focussing on theoretical and empirical work, combining doctrinal and non-doctrinal analysis for data interpretation. The findings indicate that the transfer of collective rights from indigenous communities to state authorities is rationalised through the omission of acknowledgement of unwritten customary law and the imposition of a positive legal framework centred on individual rights rather than collective rights. In contrast, the state acknowledges indigenous land rights to a restricted and contingent extent, contingent upon indigenous communities substantiating their rights within the framework of the state's legal system, maintaining occupation of their ancestral lands, and ensuring that such rights do not impede the state's business and economic interests.